MATHEMATICAL MODEL FOR THE INVESTIGATION OF HYPOXIC STATES IN THE HEART MUSCLE AT VIRAL DAMAGE - N. I. Aralova (National Academy of Sciences of Ukraine and Palladin Institute of Biochemistry of the National Academy of Sciences of Ukraine., 2021)
The main complications of organism damaged by SARS-CoV-2 virus are various cardiovascular system lesions. As a result, the secondary tissue hypoxia is developed and it is relevant to search the means for hypoxic state alleviation. Mathematical modeling of this process, followed by the imitation of hypoxic states development, and subsequent correction of hypoxia at this model may be one of the directions for investigations.